Qualidade de coordenadas geodésicas em diferentes comprimentos de linha base - Sanchotene, Evelyn Passos (2018)
RBMC is the most important active reference network in the country. Its stations continually collect the GNSS observables, being the same, the main link of connection with international networks and with the systems of reference adopted globally. Knowing that the State of São Paulo has the highest concentration of RBMC stations, a study was carried out to determine the geodetic coordinates of three RBMC stations from other RBMC stations. The stations used were (SPAR-99540, SPBR-99608, SPDR-99586, SPFE-99596, SPFR-99538, ILHA-96037, SPJA-99539, SPPI-99588, PPTE-93900, SJRP-96042, SJSP PPTE-93900, SPJA-99539 and SJSP-91537), the choice of these stations was due to the geographic distribution of each, because they State, which will generate baseline processing of lengths ranging from 70km to 800km covering a large portion of the state. The processing was performed in the GNSS Solutions software, for the data of July and August of 2018, two stations were processed at a time, always maintaining fixed one of the three stations to be determined and only occurring a variation between the other stations, this process it was repeated for the three seasons as well. The processing resulted in 26 coordinates for each of the three stations, 13 coordinates for the month of August and the other 13 for the month of July. The coordinates obtained were compared, with the official coordinates of the IBGE, in order to analyze the accuracy and precision as a function of the baseline length. Verifying with 95% significance that the accuracies within the longitude as well as the latitude are a linear function of the length of the baseline. However, the accuracy does not represent a function in relation to the length of the baseline due to the long occupation time of 24 hours.